Fibrinogen depletion after plasma-dilution: impairment of proteolytic resistance and reversal via clotting factor concentrates - He, Shu; Johnsson, Hans; Zabczyk, Michal; Hultenby, Kjell; Wallen, Håkan; Blombäck, Margareta (Thrombosis and Haemostasis, 2014)
In trauma patients, resuscitation treatment of intravascular volume may cause haemodilution including blood cell- and plasma-dilution. After plasma-dilution, fibrinogen is the first factor that decreases to critically low concentrations. Fibrin formed in lowered levels is susceptible to fibrinolysis, a natural forerunner for bleeding. To assess whether a fibrinogen concentrate or a factor XIII (FXIII) concentrate can reverse the impairment of fibrin properties after plasma dilution, different laboratory methods were used to determine thrombin generation and fibrin quantity/quality in a normal plasma sample diluted in vitro. Coagulation and clot lysis by plasmin were triggered with tissue factor and rt-PA, respectively. We found that while the endogenous thrombin potential (ETP) was unaffected after plasma-dilution due to postponement of thrombin decay, levels of fibrinogen and hence fibrin were decreased in dilution degree-dependency. The imbalance between influence of the dilution on thrombin activity and fibrin formation brought unexpected outcomes of fibrin properties: the formed clots favoured the degradation by plasmin but the fibrin networks remained tighter/less permeable. This proteolytic tendency was partly overturned by the fibrinogen concentrate added (total fibrinogen ≥ 2 g/l), and much more affected if used in combination with tranexamic acid (a fibrinolysis inhibitor) at small doses. No reversal effect resulted from the FXIII concentrate added. We conclude that plasma-dilution did reduce the proteolytic resistance of formed clots. The fibrinogen concentrate, better together with small doses of tranexamic acid, may reverse the impairment of fibrin property. The FXIII concentrate is not effective in this regard in our in vitro model using platelet-poor plasma.
Keywords: Plama dilution; coagulopathy; fibrin proteolysis; fibrinogen concentrate; FXIII concentrate; tranexamic acid